2012
DOI: 10.1155/2012/823095
|View full text |Cite
|
Sign up to set email alerts
|

Role of Mean Platelet Volume in Diagnosis of Childhood Acute Appendicitis

Abstract: Introduction. Acute appendicitis is the leading cause of abdominal pain in children requiring emergency surgical intervention. The aim of this study is to investigate the diagnostic value of MPV in early diagnosis of acute appendicitis cases in pediatric age group. Methods. This study was performed retrospectively. Three hundred five patients operated on with the diagnosis of appendicitis and pathologically found to be acute appendicitis were classified as Group 1 and 305 healthy children were classified as co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
49
4
10

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(68 citation statements)
references
References 30 publications
(13 reference statements)
3
49
4
10
Order By: Relevance
“…Four studies stated that the MPV was lower in AA patients than in controls, whereas one study reported the opposite finding [12][13][14][15]17]. Furthermore, the sixth study showed no significant difference between the 2 groups [16]. The general properties of these studies are shown in table 4.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Four studies stated that the MPV was lower in AA patients than in controls, whereas one study reported the opposite finding [12][13][14][15]17]. Furthermore, the sixth study showed no significant difference between the 2 groups [16]. The general properties of these studies are shown in table 4.…”
Section: Discussionmentioning
confidence: 97%
“…In the literature, studies have investigated the relationships between MPV and many diseases such as stroke, myocardial infarction, pulmonary embolus, pancreatitis, diabetes mellitus, cancer, sepsis, hypertensive crisis, ulcerative colitis, ankylosing spondylitis and rheumatoid arthritis [2][3][4][5][6][7][8][9][10][11]. Recently, MPV has been reported to be helpful in the diagnosis of AA [12][13][14][15][16][17]. In this study, we examined the diagnostic value of MPV for AA.…”
mentioning
confidence: 99%
“…Platelet activation is a link in the pathophysiology of diseases prone to thrombosis and inflammation. Some studies have assessed the role of the MPV values in cases with AA (8)(9)(10)(11) however these studies are contradictory. While some authors reported lowered MPV values in patients with acute appendicitis (8), other studies have reported increased MPV values (9).…”
Section: Discussionmentioning
confidence: 99%
“…MPV has been shown to reflect inflammatory burden. Additionally, the relationship between MPV values and AA has been investigated in different clinical studies yet the results are inconsistent (8)(9)(10)(11). Red cell distribution width (RDW) is an easy-tomeasure part of complete blood count, showing variability of size of circulating erythrocytes.…”
mentioning
confidence: 99%
“…Unlike these studies, Uyanik et al 20 have reported that MPV has no diagnostic value in pediatric acute appendicitis cases and Narci et al 21 have found that MPV were higher in adult patients with acute appendicitis than the control group. Our results agree with those by Uyanik et al They have considered that the frequency of inflammatory events and the difficulty of their identification in pediatric ages may have caused overlooking of the presence of other inflammatory cases in healthy control group, and this may have caused lower MPV and erroneous statistics in this group.…”
Section: Discussionmentioning
confidence: 95%